PERAN WORLD WIDE FUND FOR NATURE ( WWF ) DALAM MENDUKUNG ASOSIASI PETANI SAWIT SWADAYA MANDIRI UNTUK MEMPEROLEH SERTIFIKASI ROUNDTABLE ON SUSTAINABLE PALM OIL ( RSPO ) - Kurnia Rizki Perangin-Angin; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain the role of World Wide Fund for Nature (WWF) in supporting the Asosiasi Petani Sawit Swadaya Mandiri to obtain the Roundtable on Sustainable Palm Oil (RSPO) certification. RSPO is a non-profit association that unites stakeholders from the 7 sectors of the palm oil to develop and implement global standards for sustainable palm oil. The area expansion of Indonesia palm oil faced national and international pro-social and environment Non Government Organization (NGO) which raised black campaign related to social and environment issues. As an environmental organization that also deals with the issue of sustainable natural resource management, WWF participating in assisting independent smallholders to change oil palm management practiced by taking into economic, social and environmental elements. WWF began operations in supporting the Asosiasi Mandiri to obtain the RSPO certification since 2014.Data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis. The author used individual-group behavior level analyze, and the research are using Constructivism perspective, International Organizations theory and also using concept of Sustainable Development. The writer also did some interviews and observations by observing and taking notes of the indications systematically and directly.The results of this research shows that the WWF has carried out its role as an international organization in supporting the sustainable development agenda in Indonesia at the national and regional levels by strengthening the role of independent smallholders in addressing sustainability issues. The roles of WWF as a motivator, facilitator, donor, and as a partner were mobilized to achieve progress in realizing the vision and mission of the Asosiasi Mandiri to contribute in sustainable palm oil practices and obtain RSPO certification.Keywords : Asosiasi Petani Sawit Swadaya Mandiri, Certification, Palm Oil, Roundtable on Sustainable Palm Oil, World Wide Fund for Nature